Incidence, Common Pathogens, and Risk Factors for Infection after Primary Anterior Cruciate Ligament Reconstruction: A Systematic Review - Schneider, Justine G.; Ormseth, Benjamin; DiBartola, Alex C.; Magnussen, Robert A.; Duerr, Robert A.; Stoodley, Paul; Flanigan, David C. (The Journal of Knee Surgery, 2023)
We sought to assess the current literature to present a comprehensive summary of the incidence, common pathogens, and risk factors for infection after anterior cruciate ligament (ACL) reconstruction. PubMed, CINAHL, EMBASE, and Scopus databases were searched for relevant studies reporting on infection after ACL reconstruction. Two reviewers independently screened the extracted studies for adherence to inclusion and exclusion criteria. Studies were selected if they reported on the incidence of infection, pathogens cultured from infected knees, or risk factors for infection after primary ACL reconstruction. Exclusion criteria consisted of studies with fewer than 100 patients or studies that included revision ACL reconstruction. Fifty studies met the inclusion and exclusion criteria, reporting on a total of 316,214 ACL reconstructions. Included studies evaluated between 123 and 104,255 patients. The overall incidence of infection was 0.60% (0.15–2.44%). The most common pathogens were Staphylococcus aureus, S. epidermidis, and coagulase-negative Staphylococci. Five studies reported that the use of hamstring autograft was a statistically significant risk factor for infection after ACL reconstruction, thus making hamstring autograft the most commonly reported risk factor. Other reported risk factors included male sex, use of immuno-suppressive medications or intraarticular steroid injections, prior knee surgery, and diabetes. Systematic review of the literature revealed that infection after ACL reconstruction remains an infrequent event with an incidence of 0.60% (0.15–2.44%). Furthermore, the most common pathogens are from the Staphylococcus genus of bacteria, comprising 84% of all culture-positive infections. Multiple risk factors have been reported for ACL reconstruction; however, statistical significance varied across studies. Together, these findings may help guide physicians in the prevention and treatment of infection after ACL reconstruction.
Keywords: ACL; reconstruction; infection; incidence; pathogens; risk factors